Investment Interest in Kota Pari Village Communities: A Study of the Influence of Investment Motivation and Knowledge - Ardian, Noni; Dwilitia, Handriyani; Darmilisani, Darmilisani; Selviani, Putri (Universitas Negeri Medan, 2023)
This study aims to investigate the impact of individual investors' investment motivation and knowledge on their desire to invest in the Indonesia Stock Exchange among residents of Kota Pari Village, PantaiCermin District, SerdangBedagai Regency. The willingness to do something is bolstered by the presence of interest, but the incentive to really do it is inextricable from the two. Knowledge is essential for taking action, as ignorance can lead to disastrous consequences. The community's lack of interest stems from their inability to learn about investment opportunities. Realizing how much room there is for growth in Indonesia's economy. The Indonesia Stock Exchange has provided numerous educational and advisory programs for investors. Research submissions showing how investment knowledge and motivation can sway people's interest in investing. The residents of Kota Pari Village in Pantai Cermin District in Serdang Bedagai Regency are hoping to raise their standard of living thanks to the findings of this study. Investing motivation and knowledge were found to have a favorable and significant effect on people's interest in investing in the Indonesia Stock Exchange in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency.